Stability Analysis on the Steeply-Inclined Small-Angle Layered Surrounding Rock Masses at the Upstream High Sidewall of a Large-Span Cavern - Jian, Chong-Lin; Xu, Ding-Ping; Zhou, Yang-Yi; Chen, Dong-Fang; Zhou, Shao-Wu; Hu, Lian-Xing; Wu, Chong; Jiang, Sen-Lin (Frontiers in Earth Science, 2022)
The underground powerhouse of China’s Wudongde hydropower station is one of the world’s underground powerhouses with the largest span and height. Because the underground powerhouse is all located in steeply-inclined layered rock masses, and the bedding plane strike of the rock mass has a small angle with the axis of the main caverns, there is a serious risk of high sidewall instability. According to the basic principles of the structurally-controlled concept, the mechanical properties of bedding planes and other discontinuities are largely attributed to this problem. A thorough investigation was conducted into the Wudongde underground powerhouse throughout the excavation process to clarify the possible mechanisms behind these failures and to realize the dynamic adjustment of construction. First, the geological conditions and mechanical properties of the rock masses in the study area were introduced in detail. The stability of the right bank underground powerhouse’s surrounding layered rock mass was then investigated using a discontinuum-based numerical method. Special attention was paid to the excavation-induced failure mechanisms of the steeply-inclined small-angle layered rock masses at the upstream high sidewall. The results show that the failure of steeply-inclined small-angle layered surrounding rock masses presents significant three-stage characteristics, i.e., 1) rock plate forms due to the unloading opening of the bedding plane; 2) rock plate cracks due to bending; and 3) rock plate buckles or slides due to crack penetration. Based on the understanding of the deformation and failure mechanisms of steeply-inclined small-angle layered rock masses, the excavation sequence needs to be optimized according to local geological conditions. In practice, it is vital to insist on the principles of excavation by thin layers and finish all the supports before the next-step excavation.